Distributed predictive control of interconnected systems based on disturbance observation. Issue 19 (22nd February 2021) - Zhou, Wei; Zhang, Wen‐An; Liu, Andong
Abstract : In this study, a distributed model predictive control (MPC) method based on extended state observer is proposed for a class of large‐scale interconnected systems by using a reduced state‐space decomposition strategy. Firstly, the full state of the system is divided into internal state and external state to decrease computation and communication burden, where the former one is used for local optimisation, and the latter one is used to exchange with its neighbours. Based on the receding optimisation strategy, a reduced state‐space decomposition iterative algorithm is proposed, and the convergence of the proposed algorithm is given. To improve the disturbance rejection capability of the system, an extended state observer is designed to estimate the disturbance by using a pole assignment method. By applying a feedforward compensation strategy, a composite controller is derived by combining with local MPC controller and compensation controller, then the input‐to‐state stability is analysed for the closed‐loop system. Finally, an example of a ship engine room power system is given to demonstrate the effectiveness of the proposed method.